Imbecilicity visualization of a nonsensically built metropolis - San Jose, Julio Romualdo B.; Romero, Riza A. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Imbecilicity: 1. a city of imbeciles. The thesis' title embodies the main focus of its proposed work -a foolishly made up word for an idiotic city built with dysfunctional infrastructures as they represent society with absurdity. The work imagines Metro Manila in the distant future -an exaggeration of its present condition of a terribly laid out city- turning the landscape into a more undesirable and chaotic wasteland. The work is actualized through an architectural scale model - a practice heavily associated with the meticulous designing of built environments. However, with inconsistent scaling, improper construction of buildings mounted upon a declining base, the work's silhouette serves as a visual reminder of the society's dystopian image and inherent downfall. The work means to satirize the ill effects of nihilism as well as epistemological and cultural depreciation as it leads to societal collapse.
Thesis (Bachelor of Fine Arts in Studio Arts)--University of the Philippines Diliman
Bibliography : pages 17-19.
Keywords: Architectural models; Nihilism